2016
DOI: 10.1590/1981-7746-sip00114
|View full text |Cite
|
Sign up to set email alerts
|

Metodologias Ativas De Ensino/Aprendizagem: Dificuldades De Docentes De Um Curso De Enfermagem

Abstract: Resumo O estudo objetivou identificar as dificuldades vivenciadas pelos docentes na implementação de metodologias ativas no curso de graduação em enfermagem de uma instituição federal localizada no Rio Grande do Norte. Tratou-se de pesquisa exploratório--descritiva com enfoque qualitativo. As entrevistas semiestruturadas foram aplicadas a vinte sujeitos nos meses de agosto e setembro de 2011 e, posteriormente, analisadas seguindo pressupostos da análise de conteúdo. As principais adversidades elencadas pelos s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
47

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 6 publications
(4 reference statements)
2
21
0
47
Order By: Relevance
“…Intervene in this process of professional naturalization demands a systematized reflection based on the deconstruction of the experience. 20 A study identified as common obstacles to apply new methodologies in the influence of the conservative methods that generates the resistance of some professionals to accept other pedagogical concepts; the rigidity of the institutions and health services; and the unknown pedagogical theories. 21 The lack of time is justified by the professors' excessive functions -which involve lesson planning, monitoring the student in the internship, targets in scientific production and so on, -these were also pointed out by the coordinators from public institutions as limited development on new teaching methods.…”
Section: S223 Nurse Training In Health In Different Regions In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervene in this process of professional naturalization demands a systematized reflection based on the deconstruction of the experience. 20 A study identified as common obstacles to apply new methodologies in the influence of the conservative methods that generates the resistance of some professionals to accept other pedagogical concepts; the rigidity of the institutions and health services; and the unknown pedagogical theories. 21 The lack of time is justified by the professors' excessive functions -which involve lesson planning, monitoring the student in the internship, targets in scientific production and so on, -these were also pointed out by the coordinators from public institutions as limited development on new teaching methods.…”
Section: S223 Nurse Training In Health In Different Regions In Brazilmentioning
confidence: 99%
“…Similar results were found in a study with professors from a nursing course in the Northeast. 20 To encounter this reality, how to build collective pedagogical projects and to form different teaching organization using active methodologies since these tasks require time, dedication and institutional affiliation? 6 how to break the fragmented curriculum structure and develop one that is, in fact, interdisciplinary, cross-sectional and able to subsidize the development of skills in the needed competence to encounter with the social reality presented to the nurses in their daily work?…”
Section: S223 Nurse Training In Health In Different Regions In Brazilmentioning
confidence: 99%
“…31,32 The implementation of the integrated curriculum by teachers implies changing the crystallized territories of knowledge, the identity of the social actors involved and their practices, considering that the translation of the PPC into teaching practice is through its personalization in teachers. 33 In the translation of the integrated curriculum there is an adaptation process, the result of which is not copying but the recontextualization of the curriculum, aligning it with the experiences and values of the teacher.…”
Section: Recontextualization Of An Integrated Curriculum Franco Ecd mentioning
confidence: 99%
“…A inclusão de estratégias pedagógicas destinadas à aquisição de conhecimentos com base na realidade favorece a aproximação entre teoria e prática dos futuros profissionais em prol de uma visão crítica de se trabalhar com problemas reais. Portanto, observa-se que o contexto atual requer a formação de enfermeiros ativos, críticos, reflexivos e criativos 14 .…”
Section: Contribuições Do Parceands Na Formação Em Enfermagemunclassified
“…Associar o pensar e o fazer, refletir o teórico e o prático, instigar o questionamento e a controvérsia, são alternativas de superação aos modelos baseados na transmissão vertical de conhecimentos 14 .…”
Section: Contribuições Do Parceands Na Construção Do Conhecimentounclassified